Heart rate monitoring using human speech spectral features - James, Alex Pappachen (Human-Centric Computing and Information Sciences, 2015)
This paper attempts to establish a correlation between the human speech, emotions and human heart rate. The study highlights a possible contactless human heart rate measurement technique useful for monitoring of patient condition from realtime speech recordings. The distance between the average peak-to-peak distances in speech Mel-frequency cepstral coefficients are used as the speech features. The features when tested on 20 classifiers from the data collected from 30 subjects indicate a non-separable classification problem, however, the classification accuracies indicate the existence of strong correlation between the human speech, emotion and heart-rates.
Keywords: heart rate; human emotions; speech signal; mel-frequency cepstral coefficients; Research Subject Categories::TECHNOLOGY::Engineering physics